History of the Zodiac - van der Waerden, B. L.
Introduction: the problem; the practical use of the signs; the Greek and Egyptian zodiac — 1. The Babylonian Zodiac: zodiacal constellations; the 12 zodiacal signs; the lrst sign; Aries or Taurus?; limiting points of signs; equinoxes and solstices, precession; worship of zodiacal signs, birth horoscopes — 2. The Greek Zodiac: general notions; names of signs; tropical or sidereal zodiac? — 3. The Egyptian Zodiac: Egyptian astronomy; the zodiac of Dendera; the zero-point of the Egyptian zodiac; hellenistic decans.